Students’ Alternative Conceptions Associated With Application of Redox Reactions in Everyday Life (Asian Education Studies, 2019)
The study explored chemistry students’ alternative conceptions associated with application of the processes of oxidation and reduction in real life context. As part of a design-based research approach, a case-study design was followed. Purposive and convenient sampling procedures were employed to select 213 senior high school students to respond to a diagnostic test. Data obtained were analysed using item difficult index, percentages, and themes. The results showed that alternative conceptions existed as preconceived notions, conceptual misunderstanding, and factual misconceptions. It is recommended that chemistry educators should select most appropriate instructional strategies to unearth and address alternative conceptions students may bring to the classroom.